PENGEMBANGAN E-WORKSHEET TERINTEGRASI PEMECAHAN MASALAH PADA MATERI LAJU REAKSI - Anisa Adliyah Gultom; Zainuddin Muchtar (Universitas Negeri Medan, 2020)
The use of android-based learning media is one of the 21st century learning style applications. By using media that have been developed, this research was also conducted to find out the improvement of student learning outcomes. The population in this study were 2 class XI IPA of SMA Negeri 1 Sidamanik, where the experimental class 1 was given an integrated e-worksheet of problem based learning and the experimental class 2 was given a power point with a direct interaction model. This research uses methods and media development (R&D). The results of the feasibility analysis of the e-worksheet on the aspect of content eligibility are 4.75; language eligibility is 4,80; the feasibility of serving is 4.82 and the feasibility of serving is 4.14. By using e-worksheets that integrate problem based learning in the reaction rate material obtained an increase in learning outcomes of 82.4% with the highest value of 95 and the lowest value of 75 both of which have passed the KKM of 70. Hypothesis testing conducted yielding tcount> ttable was 3.88 > 2,042. It can be concluded that through the development of this media can improve student learning outcomes.